Spectacular suffering: Transgressive performance in penal activism - Corcoran, Mary (Theoretical criminology, 2020)
The spectacle of the body in pain has long functioned heuristically in crime and justice. Within this phenomenon sits a counter-cultural tradition of re-enacting outrages in public view to rally against injustices. This article starts from the established claim that bodily suffering comprises a core matter of humanitarian campaigning. However, if ‘spectacular suffering’ has predominantly been discussed as a visual experience, this article examines its performative aspects. Transgressive performance is evident in demonstrations of forced-feeding, hunger strikes, self-immolation and lip-sewing carried out by prisoners or by their intermediaries with a view to publicizing their cause. During such exhibitions, the body in pain becomes a heuristic device for converting suffering into a medium for public consumption. However, tropes of corporal suffering are susceptible to cultural contestation and resistance from spectators. These possibilities call the publicity of suffering into question as an inherently progressive strategy.